Birds of Prey. Murder and mystery - Simone, Gail (Birds of Prey, 2024)
"When a bullet to the spine left her without the use of her legs, and unable to continue her career as Batgirl, Barbara Gordon used her computer expertise and photographic memory to become Oracle-the all seeing information broker assisting Gotham's heroes behind the scenes. Now joined by Black Canary, Huntress, and others, she's taken on a more proactive role in crime fighting as leader of the Birds of Prey. Whether they're sparring with Lady Shiva, taken hostage by Savant, or facing multiple murder attempts from Cheshire, this team of superwomen navigate a dangerous game, chasing down super-villains when one wrong step could be deadly!" -- Back cover.